An evolutionary framework for treating pediatric sarcomas. Issue 11 (16th March 2020) - Reed, Damon R.; Metts, Jonathan; Pressley, Mariyah; Fridley, Brooke L.; Hayashi, Masanori; Isakoff, Michael S.; Loeb, David M.; Makanji, Rikesh; Roberts, Ryan D.; Trucco, Matteo; Wagner, Lars M.; Alexandrow, Mark G.; et al.
Abstract : Lessons from extinction can be used in trials designed to pursue a cure for cancer. When cancer cannot be cured, similar strategies may be unwise, and strategies that leverage the adaptations of cancer to therapy should be considered.